Lawyers' Work in between Private and Public: The Case of Directive (EU) 2019/1023 Implementation in Portugal - Santos, S. (7th Global Meeting on Law & Society, 2022)
Directive (EU) 2019/1023 on preventing restructuring frameworks, insolvency and discharge of debt is a result of a European policy regarding the creation of a European internal market based on a bundle of rules that each member state should adopt intertwining with their national legal frame or creating new legislation. Member states were given a period to adopt the new legislation and to communicate with the European Commission on possible difficulties and delays. These periods of legislative creation are of special importance on the study of how lawmakers combine different and conflictual positions and points of view, select potential interlocutors, adopt solutions. In contemporary societies, the legislative procedure is complex with the intervention of actors from the private sector, universities, trade unions, NGO and state central and local institutions. Lawyers represent a major player operating at the European and national field, writing and participating in discussion forums, counseling clients and lobbying. In another layer of analysis, the political situation and government stability influence the process by conditioning or opening the negotiation to different players and their representatives. In the current situation, Portugal had a minority left-wing government with parliament support from other left-wing political parties and, after the failure to approve the 2022 state general budget, Parliament was dissolved and new legislative elections were scheduled for January 30, 2022. The implementation of the directive occurs in this new scenario of political turbulence. In this paper, we aim to describe the process focusing our analysis on changes implemented in article 17.H - defines the guarantees of investors and partners that wish to inject capital in a company in financial difficulties or in process of restructuring. For that purpose, we collected interviews with legal actors and different materials (legal texts, jurisprudence, published opinion, etc.).